The adiponectin receptor AdipoR2 and its Caenorhabditis elegans homolog PAQR-2 prevent membrane rigidification by exogenous saturated fatty acids. - Ranjan Devkota; Emma Svensk; Mario Ruiz; Marcus Ståhlman; Jan Borén; Marc Pilon (PLoS Genetics, 2017)
Dietary fatty acids can be incorporated directly into phospholipids. This poses a specific challenge to cellular membranes since their composition, hence properties, could greatly vary with different diets. That vast variations in diets are tolerated therefore implies the existence of regulatory mechanisms that monitor and regulate membrane compositions. Here we show that the adiponectin receptor AdipoR2, and its C. elegans homolog PAQR-2, are essential to counter the membrane rigidifying effects of exogenously provided saturated fatty acids. In particular, we use dietary supplements or mutated E. coli as food, together with direct measurements of membrane fluidity and composition, to show that diets containing a high ratio of saturated to monounsaturated fatty acids cause membrane rigidity and lethality in the paqr-2 mutant. We also show that mammalian cells in which AdipoR2 has been knocked-down by siRNA are unable to prevent the membrane-rigidifying effects of palmitic acid. We conclude that the PAQR-2 and AdipoR2 proteins share an evolutionarily conserved function that maintains membrane fluidity in the presence of exogenous saturated fatty acids.